Arabidopsis LFR, a SWI/SNF complex component, interacts with ICE1 and activates ICE1 and CBF3 expression in cold acclimation - Ma, Tian; Wang, Shuge; Sun, Cunyi; Tian, Jiawang; Guo, Hong; Cui, Sujuan; Zhao, Hongtao (Frontiers in Plant Science, 2023)
Low temperatures restrict the growth and geographic distribution of plants, as well as crop yields. Appropriate transcriptional regulation is critical for cold acclimation in plants; however, the role of the SWI/SNF chromatin remodeling complex (CRC), an important epigenetic regulator of transcription, in cold acclimation is unknown. In this study, we found that the mutation of Leaf and flower related (LFR), a SWI/SNF CRC component in Arabidopsis (Arabidopsis thaliana), resulted in hypersensitivity to freezing stress in plants with or without cold acclimation, and this defect was successfully complemented by LFR. The expression levels of CBFs and COR genes in cold-treated lfr-1 mutant plants were lower than those in wild-type plants. Furthermore, LFR was found to interact directly with ICE1 in yeast and plants. Consistent with this, LFR was able to directly bind to the promoter region of CBF3, a direct target of ICE1. LFR was also able to bind to ICE1 chromatin and was required for ICE1 transcription. Together, these results demonstrate that LFR interacts directly with ICE1 and activates ICE1 and CBF3 gene expression in response to cold stress. Our work enhances our understanding of the epigenetic regulation of cold responses in plants.